The certified quality inspector handbook - Walker, H. Fred, 1963-; Elshennawy, Ahmad K.; Gupta, Bhisham C., 1942-; McShane-Vaughn, Mary, 1963- (ASQ Quality Press, 2019)
"Book is a handbook and reference for working certified quality inspectors as well as a study guide for those preparing to sit for their CQI exam, covering such topics as basic math, algebra, geometry, and trigonometry, measurement systems, gages and inspection equipment, calibration and MSA, blueprints and GDT, sampling, statistical process control, and quality improvement, auditing, tools, and techniques"--